Дослідження частотної характеристики коефіцієнта екранування - Коломоєць, Р. Ю. (ХНУРЕ, 2019)
The frequency characteristic of the shrinkage factor for a metal screen version is investigated. The conditions of the minimum of this characteristic and the influence of the main screening factors - reflection, absorption and multiple reflection are found. It is established that in the low-frequency region the main screening factor is multiple reflection, and in the high-frequency region, it is a superficial effect.